Subthalamic and Cortical Local Field Potentials Associated with Pilocarpine-Induced Oral Tremor in the Rat - Long, Lauren L.; Podurgiel, Samantha J.; Haque, Aileen F.; Errante, Emily L.; Chrobak, James J.; Salamone, John D. (Frontiers in Behavioral Neuroscience, 2016)
Tremulous jaw movements (TJMs) are rapid vertical deflections of the lower jaw that resemble chewing but are not directed at any particular stimulus. In rodents, TJMs are induced by neurochemical conditions that parallel those seen in human Parkinsonism, including neurotoxic or pharmacological depletion of striatal dopamine, dopamine antagonism, and cholinomimetic administration. Moreover, TJMs in rodents can be attenuated by antiparkinsonian agents, including L-DOPA, dopamine agonists, muscarinic antagonists, and adenosine A2A antagonists. In human Parkinsonian patients, exaggerated physiological synchrony is seen in the beta frequency band in various parts of the cortical/basal ganglia/thalamic circuitry, and activity in the tremor frequency range (3-7 Hz) also has been recorded. The present studies were undertaken to determine if tremor-related local field potential (LFP) activity could be recorded from motor cortex or subthalamic nucleus during the TJMs induced by the muscarinic agonist pilocarpine, which is a well-known tremorogenic agent. Pilocarpine induced a robust TJM response that was marked by rhythmic electromyographic activity in the temporalis muscle. Compared to periods with no tremor activity, TJM epochs were characterized by increased LFP activity in the tremor frequency range in both neocortex and subthalamic nucleus. Tremor activity was not associated with increased synchrony in the beta frequency band. These studies identified tremor-related LFP activity in parts of the cortical/basal ganglia circuitry that are involved in the pathophysiology of Parkinsonism. This research may ultimately lead to identification of the oscillatory neural mechanisms involved in the generation of tremulous activity, and promote development of novel treatments for tremor disorders.